Evaluation of an Unplanned School Closure in a Colorado School District: Implications for Pandemic Influenza Preparedness. (4th March 2015) - Epson, Erin E.; Zheteyeva, Yenlik A.; Rainey, Jeanette J.; Gao, Hongjiang; Shi, Jianrong; Uzicanin, Amra; Miller, Lisa
Abstract: Objective: From January 29 through February 5, 2013, a school district outside metropolitan Denver, Colorado, was closed because of absenteeism related to influenza-like illness (ILI) among students and staff. We evaluated the consequences and acceptability of the closure among affected households. Methods: We conducted a household survey regarding parent or guardian employment and income interruptions, alternative child care arrangements, interruption of noneducational school services, ILI symptoms, student re-congregation, and communication preferences during the closure. Results: Of the 35 (31%) of 113 households surveyed, the majority (28 [80%]) reported that the closure was not challenging. Seven (20%) households reported challenges: 5 (14%) reported that 1 or more adults missed work, 3 (9%) reported lost pay, and 1 (3%) reported challenges because of missed subsidized school meals. The majority (22 [63%]) of households reported that a hypothetical 1-month closure would not represent a problem; 6 of 8 households that did anticipate challenges reported that all adults worked outside the home. The majority (58%) of students visited at least 1 outside venue during the closure. Conclusions: A brief school closure did not pose a major problem for the majority of the affected households surveyed. School and public health officials should consider the needs of families in which all adults work outside the home when creating school closure contingency plans. ( Disaster Med Public Health Preparedness . 2015;9:4-8)